Faktor-Faktor Yang Berhubungan Dengan Kelengkapan Imunisasi Lanjutan Pada Anak Bawah Dua Tahun (Baduta) Di Wilayah Kerja Puskesmas Nilam Sari Tahun 2026 - Syafia Alia; Yasherly Bachri; Anisa Sri Utami (Borneo Nursing Journal (BNJ), 2026)
Follow-up immunization is an essential component of the national immunization program aimed at maintaining children's immunity against vaccine-preventable diseases. The coverage of follow-up immunization in Bukittinggi remains below the national target, including in the working area of Nilam Sari Public Health Center. This study aimed to identify factors associated with the completeness of follow-up immunization among children under two years of age. A quantitative cross-sectional study was conducted involving 41 mothers selected using purposive sampling. Data were collected using structured questionnaires and analyzed using univariate and Chi-square tests. The results showed that most respondents had high educational levels (82.9%), good knowledge (51.2%), and perceived good roles of health workers (58.5%), while inadequate family support remained high (56.1%). Only 36.6% of children had completed follow-up immunization. Maternal education was not significantly associated with immunization completeness (p=0.179). However, maternal knowledge (p=0.005), the role of health workers (p=0.005), and family support (p=0.004) were significantly associated with follow-up immunization completeness. Strengthening health education, improving the role of health workers, and increasing family involvement are recommended to improve follow-up immunization coverage. Keywords: follow-up immunization, children under two years, knowledge, health workers, family support